2022
DOI: 10.1021/acs.jpcc.2c00336
|View full text |Cite
|
Sign up to set email alerts
|

Mitigation of Surface Oxidation in Sb2Se3 Thin Films Via Te Doping: An Effective Strategy Towards Realization of Efficient Electronic Devices

Abstract: Sb2Se3 and Te-doped Sb2Se3 films of ∼250 nm film thickness were deposited using a facile thermal evaporation technique from the bulk powder synthesized via the melt quenching technique. Thermogravimetric analysis of pure and Te-doped Sb2Se3 alloys in bulk form indicates decomposition of the alloys in the 303–673 K temperature range. The X-ray diffraction pattern revealed single-crystalline orthorhombic phase stabilization of as-prepared alloys in bulk as well as in the annealed thin films. Phase formation is a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 55 publications
0
12
0
1
Order By: Relevance
“…Another study of Te doping in Sb 2 Se 3 solar cells was reported by employing the thermal evaporation technique. 71 As compared to the control device without doping, the device with an optimal doping concentration of 0.08 at% showed an unusual increase in optical band gap from 1.46 to 1.65 eV, which was then ascribed to the crystallization of multiple Sb–Se phases with higher bond energies. However, the conductivity of doped films was reduced to 1.22 × 10 −7 Ω −1 cm −1 compared to undoped Sb 2 Se 3 2.55 × 10 −7 Ω −1 cm −1 .…”
Section: Extrinsic Doping Approachesmentioning
confidence: 92%
See 1 more Smart Citation
“…Another study of Te doping in Sb 2 Se 3 solar cells was reported by employing the thermal evaporation technique. 71 As compared to the control device without doping, the device with an optimal doping concentration of 0.08 at% showed an unusual increase in optical band gap from 1.46 to 1.65 eV, which was then ascribed to the crystallization of multiple Sb–Se phases with higher bond energies. However, the conductivity of doped films was reduced to 1.22 × 10 −7 Ω −1 cm −1 compared to undoped Sb 2 Se 3 2.55 × 10 −7 Ω −1 cm −1 .…”
Section: Extrinsic Doping Approachesmentioning
confidence: 92%
“…10,31,39,67 Whereas Hobson et al revealed unintentional introduction of chlorine (Cl) impurities present in the purchased source material formed n-type Sb 2 Se 3 absorber. 36 Furthermore, due to the presence of extrinsic dopants such as iodine (I) 44,68 and tellurium (Te), 32,[69][70][71] the possibility of formation of n-type devices with high efficiencies also exists. Hence, it's vitally important to consider the source of the Sb 2 Se 3 material and any impurities that may be present in the growth or processing environment, as Sb 2 Se 3 in solar cells can behave as both p-type or n-type absorbers.…”
Section: Introductionmentioning
confidence: 99%
“…Doping is an effective strategy for modifying physical and electronic properties by generating benign defects, improving conductivity, regulating crystallization, and suppressing surface or grain boundary defects. Various types of dopants including Na, [7] Fe, [8] K, [9] Te, [10] S, [11] , Bi, [12] and Cu, [13,14] have been extensively explored to improve the solar cell and PEC performance of Sb2Se3 photocathodes. For example, Te doping in Sb2Se3 solar cells, prepared through spincoating, has been shown to effectively suppress deep-level defects by regulating the atomic ratio of Se/Sb.…”
Section: Introductionmentioning
confidence: 99%
“…Ma et al [ 13 ] reported Te-doped Sb 2 Se 3 thin film synthesized by spin-coating, which indicated that Te-doping can successfully minimize the deep-level defects in the Sb 2 Se 3 thin film by optimizing the change in Sb/Se atomic ratios. Rahman et al [ 14 ] studied the Te-doped Sb 2 Se 3 thin film obtained by thermal evaporation from the bulk powder prepared using the melt quenching technique. A reduction in surface oxidation may be detected in Sb 2 Se 3 thin films, and the DC conductivity of the Te-doped Sb 2 Se 3 thin film is in the region of 10 −7 Ω −1 cm −1 at 308.5 K, which is ten times more than the conductivity of pristine Sb 2 Se 3 films that had previously been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Rahman et al [14] studied the Te-doped Sb 2 Se 3 thin film obtained by thermal evaporation from the bulk powder prepared using the melt quenching technique. A reduction in surface oxidation may be detected in Sb 2 Se 3 thin films, and the DC conductivity of the Te-doped Sb 2 Se 3 thin film is in the region of 10 −7 Ω −1 cm −1 at 308.5 K, which is ten times more than the conductivity of pristine Sb 2 Se 3 films that had previously been reported.…”
Section: Introductionmentioning
confidence: 99%